Rapid Flame-Annealed CuFe2O4 as Efficient Photocathode for Photoelectrochemical Hydrogen Production - Park, Sangwook; Baek, Ji Hyun; Zhang, Liang; Lee, Jae Myeong; Stone, Kevin H.; Cho, In Sun; Guo, Jinghua; Jung, Hyun Suk; Zheng, Xiaolin (ACS Sustainable Chemistry and Engineering, 2019)
Copper ferrite (CuFe2O4) possesses an indirect bandgap in the range of 1.54-1.95 eV. It is used as an attractive p-type photocathode in photoelectrochemical (PEC) water splitting, and theoretically it can yield a maximum photocurrent density of ∼27 mA/cm2 and a maximum solar-to-hydrogen conversion efficiency of ∼33%. To date, only a few reports have been published on CuFe2O4 photocathodes with very low-photocurrent densities, with a maximum value of 0.4 mA/cm2 at 0.4 V vs RHE. Herein, we prepared a CuFe2O4 photocathode on FTO glass with the sol-gel method followed by either high-temperature flame annealing or furnace annealing. We found that the flame-annealed CuFe2O4 photocathode generated a photocurrent density of 1.82 mA/cm2 at 0.4 V vs RHE that is approximately 3.5 times higher than the furnace-annealed CuFe2O4 (0.52 mA/cm2). This photocurrent density is also higher than those of all the reported CuFe2O4 photocathodes, and any Cu containing ternary oxide (Cu-M-O, M: Fe, Bi, V, and Nb) photocathode (0.1-1.3 mA/cm2 at 0.4 V vs RHE). An improved PEC performance of the flame-annealed CuFe2O4 photocathode is elicited owing to the beneficial effects of flame annealing on the physical, optical, and electrical properties of CuFe2O4. Flame annealing enhances the light absorption property of the CuFe2O4 photocathode by slightly reducing the bandgap, and by forming a thicker film with increased porosity. Flame annealing also reduces the oxygen vacancy concentration in CuFe2O4, thus facilitating charge transport and interfacial charge transfer processes. Moreover, flame annealing requires only 16 min, which is much shorter than the time required for furnace annealing (∼9 h). These results demonstrate that flame annealing is a rapid and effective means for fabricating metal oxide photoelectrodes with an enhanced PEC water splitting performance.
Keywords: CuFe2O4; High-temperature flames; Interfacial charge transfer; Oxygen vacancy concentration; Photoelectrochemical hydrogen production; Photoelectrochemical water splitting; Photoelectrochemicals; Solar-to-hydrogen conversions; CuFe2O4; Flame synthesis; Hydrogen production; Photoelectrochemical water splitting